UINUMO URHUKATA. Etno-biomaterial de la meseta P’urhépecha propuesta de diseño experimental - Ramírez Campanur, Xóchitl Celeste (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
By using organic waste in large quantities, in this case pine leaves, prevents them from becoming pollutants during forest fires, which promotes environmental sustainability, conserving natural resources and contributing to environmental protection, helping to prevent air pollution. The leaves of pine trees, also known as needle trees, are constantly renewed as part of the natural cycle of the tree; the dry leafage that falls to the forest soil, also known as uinumo within the P'urhépecha plateau, is a material that helps to the conservation of the forest, but it is also a natural material in abundance that is highly flammable in the dry season and is one of the factors that contribute to the generation and expansion of forest fires within this region, in addition to being one of the problems that afflicts these communities. Currently, uinumo is used as raw material for the elaboration of handicrafts, made mainly by women from forest communities in the state of Michoacán, and within the region of the P'urhépecha plateau. In this context, the project "ethno-biomaterial from the P'urhépecha plateau; experimental design proposal" takes place, in which, the purpose is to take advantage of the abundance of uinumo material. It seeks to explore with this material the experimental design of biomanufacturing, using organic components, and the natural abundances available in the region in order to propose new alternatives and revalue these natural abundance wastes.

Al aprovechar los desechos orgánicos en gran cantidad, en este caso las hojas de pino, impide se conviertan en contaminante durante los incendios forestales, Lo cual promueve la sostenibilidad ambiental, conservar los recursos naturales y contribuir a la protección del medio ambiente, ayudando a prevenir la contaminación del aire. Las hojas de los pinos, también conocidas como acículas, se renuevan constantemente como parte del ciclo natural del árbol; el follaje seco que cae al suelo, también conocido como uinumo dentro de la meseta P’urhépecha, es un material que ayuda a la conservación del bosque, pero también es un material natural en abundancia que es altamente inflamable en la época seca del año y es uno de los factores que contribuyen a la generación y expansión de los incendios forestales dentro de esta región: siendo uno de los problemas que aqueja a estas comunidades. Actualmente el uinumo, sirve de materia prima para la elaboración de artesanías, hechas principalmente por mujeres de comunidades forestales, en el estado de Michoacán, y dentro de la región de la meseta P’urhépecha. En este contexto surge el proyecto “etno-biomaterial de la meseta P´urhépecha; propuesta de diseño experimental” que busca el aprovechamiento de abundancia de material del uinumo. Se busca explorar con este material el diseño experimental de la biofabricación, utilizando componentes orgánicos, y las abundancias naturales a disposición de la región con la finalidad de proponer nuevas alternativas y revalorizar estos desechos naturales de abundancia.
Facultad de Arquitectura. Maestría en diseño avanzado
Keywords: info:eu-repo/classification/cti/4; FA-M-2024-0376; Biomaterial; Uinumo; Diseño experimental; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18629